تعليم اللغة العربية لموظفي وعمال شؤون المساجد في كوالالمبور وسلانجور - Khairun Nisaa binti Mohd (Kulliyyah of Languages and Management, International Islamic Universiti Malaysia, 2017)
This study aims to investigate the needs of mosque officers and workers for learning Arabic Language and to present the topics related to mosque matters. These are clarified through the four skills of language especially the speaking skill. The research methodology combined descriptive, survey and analytical approaches. Questionnaires were distributed and interviews were conducted to obtain more information from four mosques in Kuala Lumpur and Selangor. The number of respondents reached seven officers, 47 workers and five tourists. After analysing the interviews and questionnaires it is clear to the researcher that they need a special academic module to aid their handling of mosque matters. An example of the module was presented based on the learners' needs, followed by training to use the terms, linguistic structures and the grammatical rules.